STUDI PERBANDINGAN ALTERNATIF PENINGGIAN ELEVASI JALAN DENGAN PENGGUNAAN BANGUNAN PROTEKSI PIPA TERHADAP BIAYA, MUTU DAN WAKTU - fauziyah, shifa; Nurjihad C, Fajar; Suwarto, Fardzanela (Jurnal Proyek Teknik Sipil, 2019)
One of the work items in the Soekarno-Hatta Airport Accessibility and Ducting Utility Project is widening the M1-M2 road. Pit test results in that area indicate that there is a 40 cm (16 ") diameter Pertamina pipeline at a depth of 0.7 m. The pipe is used to flow aircraft fuel so it is not possible to be relocated, this condition is called road crossing pipeline. Alternative solutions to overcome these problems are road elevation and the making of pipe protection from concrete. Road elevation costs as much as Rp 13,626,916,287.02 compared to alternative construction of pipeline protection amounting to Rp 23,200,588,370. The time for completing the elevation of the road is faster, which is around 47 weeks, while the implementation of the road and making pipeline protection takes 61 weeks. In terms of quality, in soil compaction during the road elevation process uses a vibroroller so that compaction is evenly distributed. Based on the comparative results in terms of cost, time and quality, the alternative solution to the problem road crossing pipeline is road elevation.